2016
DOI: 10.1016/j.tiv.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress pathways involved in cytotoxicity and genotoxicity of titanium dioxide (TiO2) nanoparticles on cells constitutive of alveolo-capillary barrier in vitro

Abstract: The health risks of nanoparticles remain a serious concern given their prevalence from industrial and domestic use. The primary route of titanium dioxide nanoparticle exposure is inhalation. The extent to which nanoparticles contribute to cellular toxicity is known to associate induction of oxidative stress. To investigate this problem further, the effect of titanium dioxide nanoparticles was examined on cell lines representative of alveolo-capillary barrier. The present study showed that all nanoparticle-expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 63 publications
(79 reference statements)
7
47
0
1
Order By: Relevance
“…In the present study, significant HUVEC apoptosis was observed from the lowest-tested concentration (1 μg/mL) of the four sizes of nano-TiO 2 , with a clear dose-effect relationship (Figure 4). This is consistent with the findings of other groups in human HepG2 cells, 20 macrophage-like THP-1 cells, 31 and several animal tissues. 16,33,34 These results suggested that induction of apoptosis is an important biological mechanism by which nano-TiO 2 exposure may cause adverse effects to human health.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, significant HUVEC apoptosis was observed from the lowest-tested concentration (1 μg/mL) of the four sizes of nano-TiO 2 , with a clear dose-effect relationship (Figure 4). This is consistent with the findings of other groups in human HepG2 cells, 20 macrophage-like THP-1 cells, 31 and several animal tissues. 16,33,34 These results suggested that induction of apoptosis is an important biological mechanism by which nano-TiO 2 exposure may cause adverse effects to human health.…”
Section: Discussionsupporting
confidence: 93%
“…29 It is now known that the intracellular approach of apoptosis is mainly initiated by the induction of p53 as a response to DNA damage induced by genotoxic agents. 29 A number of studies have shown that nano-TiO 2 can induce DNA damage and adversely affect both major DNA repair mechanisms: base excision repair and nucleotide excision repair, showing a genotoxic potential to human cells 10,31,[42][43][44][45] and animal models. 24,46,47 We also found that the four sizes of nano-TiO 2 could induce significant DNA damages and micronuclei in human BEAS-2B cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the frequently observed paradigms for NP‐mediated toxicity include oxidative stress and genetic damage . Production of reactive oxygen species (ROS) upon exposure to NPs is being considered as the primary underlying cause of nano toxicology, which in turn leads to DNA damage and even cell death . Hence, the genotoxicity of the MgO NPs and MPs was assessed by comet assay in peripheral blood leukocytes (PBL), liver and bone marrow, micronucleus test (MNT) in bone marrow cells and peripheral blood (PB) and chromosomal aberrations (CAs) test in the bone marrow cells to determine mitotic index (MI) and aberrations of chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, TiO 2 ‐NPs were found to elicit a significant increase of oxidative DNA damage in human lymphocytes, BEAS‐2B, A549, HepG2, and HEK293 cells in vitro and in the mice PBMCs, liver cells, and lung cells in vivo, and micronuclei and chromosomal aberrations in both plant and human lymphocytes . In the literature, however, the observed genotoxic potencies of ENPs were cell‐type‐dependent; inconsistent and even contradictory consequences were often obtained in different types of cells . This highlights the need to study the genotoxicity of ENPs in various types of cells on a case‐by‐case basis.…”
Section: Introductionmentioning
confidence: 99%
“…38 In the literature, however, the observed genotoxic potencies of ENPs were cell-type-dependent; inconsistent and even contradictory consequences were often obtained in different types of cells. 9,28,30,[39][40][41][42][43][44] This highlights the need to study the genotoxicity of ENPs in various types of cells on a case-by-case basis. Our previous work has found that TiO 2 -NPs could induce a significant apoptosis in human umbilical vein endothelial cells (HUVECs) in culture.…”
mentioning
confidence: 99%